Hypernasality associated with basal ganglia dysfunction: evidence from Parkinson’s disease and Huntington’s disease - Novotný,Michal; Rusz,Jan; Čmejla,Roman; Růžičková,Hana; Klempíř,Jiří; Růžička,Evžen (PeerJ, 2016)
Background Although increased nasality can originate from basal ganglia dysfunction, data regarding hypernasality in Parkinson’s disease (PD) and Huntington’s disease (HD) are very sparse. The aim of the current study was to analyze acoustic and perceptual correlates of velopharyngeal seal closure in 37 PD and 37 HD participants in comparison to 37 healthy control speakers. Methods Acoustical analysis was based on sustained phonation of the vowel /i/ and perceptual analysis was based on monologue. Perceptual analysis was performed by 10 raters using The Great Ormond Street Speech Assessment ’98. Acoustic parameters related to changes in a 1/3-octave band centered on 1 kHz were proposed to reflect nasality level and behavior through utterance. Results Perceptual analysis showed the occurrence of mild to moderate hypernasality in 65% of PD, 89% of HD and 22% of control speakers. Based on acoustic analyses, 27% of PD, 54% of HD and 19% of control speakers showed an increased occurrence of hypernasality. In addition, 78% of HD patients demonstrated a high occurrence of intermittent hypernasality. Further results indicated relationships between the acoustic parameter representing fluctuation of nasality and perceptual assessment (r = 0.51, p < 0.001) as well as the Unified Huntington Disease Rating Scale chorea composite subscore (r = 0.42, p = 0.01). Conclusions In conclusion the acoustic assessment showed that abnormal nasality was not a common feature of PD, whereas patients with HD manifested intermittent hypernasality associated with chorea.
Keywords: Nasality; Parkinson Disease; Huntington Disease; Dysarthria; 1/3-octave spectra; Acoustic analysis; Speech disorders